2018
DOI: 10.1186/s12906-018-2102-3
|View full text |Cite
|
Sign up to set email alerts
|

Subchronic toxicity, immunoregulation and anti-breast tumor effect of Nordamnacantal, an anthraquinone extracted from the stems of Morinda citrifolia L

Abstract: BackgroundMorinda citrifolia L. that was reported with immunomodulating and cytotoxic effects has been traditionally used to treat multiple illnesses including cancer. An anthraquinone derived from fruits of Morinda citrifolia L., nordamnacanthal, is a promising agent possessing several in vitro biological activities. However, the in vivo anti-tumor effects and the safety profile of nordamnacanthal are yet to be evaluated.MethodsIn vitro cytotoxicity of nordamnacanthal was tested using MTT, cell cycle and Anne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 31 publications
1
29
0
Order By: Relevance
“…Numerous papers have reported that extract or juice from fruit of noni is able to modulate functional role of immune cells such as NK cells, CD4 + T‐cells, CD8 + T‐cells, and B‐cells under disease conditions such as the tumor xenograft model, Leishmania amazonensis infection model, paw and ear edema model, picryl chloride‐induced contact dermatitis model, 12‐O‐tetradecanoylphorbol‐13‐acetate‐induced inflammation model, alcohol‐induced liver damage model, 12‐O‐tetradecanoylphorbol‐13‐acetate‐induced skin inflammation model, and DSS‐induced colitis model (Abu et al, ; Akihisa et al, ; Almeida‐Souza et al, ; Almeida‐Souza et al, ; Chang et al, ; Coutinho de Sousa et al, ; Li et al, ; Lim et al, ; Murata et al, ). In this study, however, we investigated the in vivo immunostimulatory activity of Mc‐eWE using mice under normal conditions, because we were curious on the immunoregulatory activity of noni fruit extract under healthy conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous papers have reported that extract or juice from fruit of noni is able to modulate functional role of immune cells such as NK cells, CD4 + T‐cells, CD8 + T‐cells, and B‐cells under disease conditions such as the tumor xenograft model, Leishmania amazonensis infection model, paw and ear edema model, picryl chloride‐induced contact dermatitis model, 12‐O‐tetradecanoylphorbol‐13‐acetate‐induced inflammation model, alcohol‐induced liver damage model, 12‐O‐tetradecanoylphorbol‐13‐acetate‐induced skin inflammation model, and DSS‐induced colitis model (Abu et al, ; Akihisa et al, ; Almeida‐Souza et al, ; Almeida‐Souza et al, ; Chang et al, ; Coutinho de Sousa et al, ; Li et al, ; Lim et al, ; Murata et al, ). In this study, however, we investigated the in vivo immunostimulatory activity of Mc‐eWE using mice under normal conditions, because we were curious on the immunoregulatory activity of noni fruit extract under healthy conditions.…”
Section: Resultsmentioning
confidence: 99%
“…The biological activity of the nordamnacanthal extracted from the stems of M. citrifolia was also checked in vitro by Abu et al. () using MTT assay, cell cycle and Annexin V/PI assays on human MCF‐7, MDA‐MB231, and 4T1 breast cancer cells. The results showed that nordamnacanthal extracted from the stems of M. citrifolia managed to reduce the viability of MCF‐7, MDA‐MB231, and 4T1 cells in a dose‐dependent manner as a higher concentration of nordamnacanthal reduced a higher degree of the viability for all the tested breast cancer cells.…”
Section: Phytotherapic Propertiesmentioning
confidence: 99%
“…ND intervention does not cause any mortality and diminishes the development of 4T1 in mice. The results suggested that ND supplementation enhanced the immunity without any adverse effects [24].…”
Section: Resultsmentioning
confidence: 94%
“…Even though noni and its products were reported for beneficial effects, some of the controversial reports also are there [18,19]. Some studies evaluated the subchronic toxicity of various part of noni plant extracts [20][21][22][23][24]. There was no literature on safety and subchronic toxicity of fermented noni fruits.…”
Section: Introductionmentioning
confidence: 99%